Exploring Cybercrime Capabilities: Variations Among Cybercrime Investigative Units - Steinmetz, Kevin F. (Criminal justice policy review, 2024)
The current analysis utilizes semi-structured qualitative interviews with sworn cybercrime detectives, civilian digital forensics analysts, and unit administrators to consider variations between cybercrime units which bear significant implications for cybercrime investigative policy and practice. The first variation observed in this study concerns differences in the structure of digital forensics assignments. Such duties may be assigned to sworn officers, civilians, sworn officers and civilian, outsourced to other departments, or a dedicated forensic lab. Second, variations between units were noted in resource availability (tools, training, and finances). These variations among cybercrime units may have implications for personnel recruitment and retention, the sophistication of cases considered by investigators, and case success.